Uji Aktivitas Ekstrak Etanol 96% Daun Senduduk Bulu (Clidemia hirta (L.) D.Don) Terhadap Khamir Candida albicans ATCC 8934 - Delyvia Clara Gita; Risky Hadi Wibowo; Camelia Dwi Putri Masrijal; Nori Wirahmi; Rose Intan Perma Sari; Oky Hermansyah (Universitas Bengkulu, 2023)
Candidiasis is an infection caused by the yeast of Candida albicans. C. albicans infection often affects the vaginal area which is known as vulvovaginal candidiasis. Candidiasis can be treated using traditional medicine or herbal medicine derived from plants, one of which is senduduk bulu plant (Clidemia hirta (L.) D.Don). This study aims to determine the phytochemical screening of the ethanol extract of Senduduk Bulu (C. hirta) leaves and to determine the anti-candidiasis activity of the ethanol extract of C. hirta leaves in inhibiting the growth of the C. albicans at concentrations of 10%, 25%, 50 % and 75%. Activity test of ethanol extract of C. hirta against C. albicans was analyzed by SPSS 25 application with ANOVA test analysis. The extract was prepared by maceration method with 96% ethanol solvent. Phytochemical screening is observed by the precipitation reaction and the color change reaction. The anti-candidiasis activity test was carried out with 3 replications using the disc diffusion method. The end result of making ethanol extract of C. hirta is a dark green viscous extract, with a yield calculation of 17.96%. Phytochemical test results showed that C. hirta contained flavonoids, saponins, tannins and steroids. C. hirta extract inhibited the growth of C. albicans. The most effective concentration of C. hirta extract in inhibiting the growth of the C. albicans was 75% with an inhibition power of 28.73 mm (very strong category).